Higher levels of serum α-Klotho are longitudinally associated with less central obesity in girls experiencing weight gain - Carreras-Badosa, Gemma; Puerto-Carranza, Elsa; Mas-Parés, Berta; Gómez-Vilarrubla, Ariadna; Gómez-Herrera, Bernat; Díaz-Roldán, Ferran; Riera-Pérez, Elena; de Zegher, Francis; Ibañez, Lourdes; Bassols, Judit; López-Bermejo, Abel (Frontiers in Endocrinology, 2023)
Introduction: Klotho is an anti-aging protein that reduces adiposity and increases caloric expenditure, among others. Although associations between secreted α-Klotho levels and obesity have been described, its relationship with central obesity and visceral fat accumulation during childhood is poorly understood. Our objective was to study the longitudinal associations between serum α-Klotho concentrations and obesity-related parameters in apparently healthy children. Subjects and methods: We studied a cohort of 208 apparently healthy school-age children (107 girls and 101 boys) assessed at baseline (mean age 8.5 ± 1.8 years) and at follow-up 4 years later. Serum α-Klotho concentrations were measured at baseline in all subjects. Obesity-related parameters, such as BMI, waist circumference, body fat, visceral fat, triglyceride levels, HOMA-IR index, and C-reactive protein were studied. Boys and girls were classified into 3 groups according to weight change between baseline and follow-up visits: weight loss, stable weight, or weight gain (based on a BMI-SDS change cut-off ˃ 0.35 SD). Results: In girls (N=107), but not in boys, we observed negative associations of serum α-Klotho protein with BMI, waist circumference, body fat, visceral fat, HOMA IR index, and C-reactive protein at baseline and also at follow-up. The associations of α-Klotho and obesity-related parameters were more evident in girls who exhibited weight gain. In such girls, multivariate regression analyses (adjusting for age, puberty and baseline weight/height ratio) showed that α-Klotho protein was negatively associated with follow-up BMI, waist circumference, and visceral fat (p = 0.003 to 0.028). For each 1 SD-increase in baseline α-Klotho, follow-up waist circumference decreased by 4.15 cm and visceral fat by 1.38 mm. Conclusions: In school-age girls, serum α-Klotho concentrations are longitudinally related to a more favorable metabolic profile. In girls experiencing weight gain, α-Klotho may prove to be a protective factor against the accumulation of visceral fat.